2001
DOI: 10.1037/h0095084
|View full text |Cite
|
Sign up to set email alerts
|

"It was just realizing…that life isn't one big horror": A qualitative study of supported socialization.

Abstract: This report describes the qualitative component of a large-scale study of supported socialization. Paralleling the recent advances made through supported housing, supported employment, and supported education, this approach seeks to increase the involvement of individuals with psychiatric disabilities in naturally occurring social and recreational activities in community settings of their choice. After a review of social relationships and psychiatric disability, we describe the Partnership Project and present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
3
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 33 publications
10
112
3
10
Order By: Relevance
“…to compare being matched with any volunteer partner with being given only a stipend and encouragement to take part in social and recreational activities~i.e., without a partner!. Qualitative findings derived from interviews with participants from this study have been reported previously~Davidson, Haglund, Stayner, Rakfeldt, Chinman, & Tebes, 2001;Davidson, Stayner, Nickou et al, 2001!. The present study examines whether or not people with psychiatric disabilities will engage in friendships when offered the opportunity and supports to do so and the extent to which these friendships impact on participants' general and social functioning, psychiatric symptoms, self-esteem, health status, well-being, and satisfaction.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…to compare being matched with any volunteer partner with being given only a stipend and encouragement to take part in social and recreational activities~i.e., without a partner!. Qualitative findings derived from interviews with participants from this study have been reported previously~Davidson, Haglund, Stayner, Rakfeldt, Chinman, & Tebes, 2001;Davidson, Stayner, Nickou et al, 2001!. The present study examines whether or not people with psychiatric disabilities will engage in friendships when offered the opportunity and supports to do so and the extent to which these friendships impact on participants' general and social functioning, psychiatric symptoms, self-esteem, health status, well-being, and satisfaction.…”
mentioning
confidence: 80%
“…Qualitative interviews were conducted with the first seven participants from each condition who agreed to participate. Results of the qualitative interviews have been described in previous publications~e.g., Davidson, Haglund, Stayner et al, 2001!.…”
Section: Methodsmentioning
confidence: 96%
“…Writes Davidson [58, p. 30]: ''Building a friendship of excellence is what will truly define one's process of recovery'' [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate economic resources influence the possibilities for social activities and social company (Barham and Hayward 1991;Davidson et al 2001). People with SMI have often been poor for a long time and have few possibilities to improve their economic situation.…”
Section: A Social Perspective -The Individual and The Environmentmentioning
confidence: 99%